Parallel computational technologies : 12th International Conference, PCT 2018, Rostov-on-Don, Russia, April 2-6, 2018, Revised selected papers /: 12th International Conference, PCT 2018, Rostov-on-Don, Russia, April 2-6, 2018, Revised selected papers. (2018) - Unknown
No abstract available